Resonant core spectroscopies of model molecular solar cells - Gibson, Andrew (2017)
This research is less the practical development of solar technology and more the fundamental understanding behind the critical adsorption bonding, electron coupling and charge transfer processes which underpin that technology. The goal of this thesis was to better understand the charge transfer dynamics in model molecular solar cells particularly nanoscale alumina lms, C60, dye molecules and their derivatives. Hence the focus of this thesis was firstly to study the charge transfer dynamics due to oxide passivation layers which form recombination barriers in DSCs and secondly to further study the core-hole decay of a charge transfer and core hole decay process which lead to a constant kinetic energy features on RPES images of C60 on Au and Ag(111).